Field notes contributed by Bery Engebretsen, spring 1992 - Engebretsen, Beryet al (1992)
List of birds and locations contributed by Bery Engebretsen. This item was submitted past the deadline for the Iowa Ornithologists' Union Quarterly Report of spring 1992. Plustek - flatbed